2009
DOI: 10.4067/s0717-95022009000300030
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Unusual Anatomy: Maxillary Central Incisor with Two Root Canals

Abstract: Success in root canal treatment is achieved after thorough cleaning and shaping followed by complete obturation of the canal system. Therefore, endodontic therapy requires specific and complete knowledge of the internal and external dental anatomy, and its variations in presentation. Such treatment may be performed in root canal systems that do not comply with the normal anatomical features described in standard textbooks. The internal anatomy of the maxillary central incisor is well known and usually presents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
(6 reference statements)
0
6
0
1
Order By: Relevance
“…Therefore, thorough knowledge of both the external and internal anatomy of teeth is of great importance for successful endodontic treatment. [2] This case report presents a striking feature of presence of extra root in the mandibular lateral incisor. Non-surgical endodontic root canal treatment was planned for all 4 mandibular incisors.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Therefore, thorough knowledge of both the external and internal anatomy of teeth is of great importance for successful endodontic treatment. [2] This case report presents a striking feature of presence of extra root in the mandibular lateral incisor. Non-surgical endodontic root canal treatment was planned for all 4 mandibular incisors.…”
Section: Introductionmentioning
confidence: 86%
“…[10] From a clinical standpoint, only by correct examination and interpretation of radiographic images the clinician can detect variations in both root and canal anatomy and be aware of them before and during endodontic procedures. [2] A variety of techniques have been used to study the internal anatomy of lower incisors. Although radiographs are unlikely to show the complexities of the root canal system such as lateral canals and eccentrically located apical foramina, but it can reveal the main anatomical features.…”
Section: Investigatorsmentioning
confidence: 99%
“…Maxillary central incisors are usually considered to have single root and one root canal [1]. While some case studies reported with two to four canals, two roots and two root canals [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…O claro entendimento da anatomia do canal radicular da dentição humana é um pré-requisito para o sucesso dos procedimentos endodônticos convencionais (GONDIM et al, 2009;RODRIGUES et al, 2009;FARAMARZI et al, 2010) e, desta maneira, faz-se necessário que o clínico compreenda não apenas a anatomia dental, mas as suas variações (ATIEH, 2008;ALMEIDA-GOMES et al, 2009), o que facilita a limpeza, modelagem e obturação dos canais radiculares (JAFARZADEH; WU, 2007).…”
Section: Revisão Da Literatura E Discussãounclassified